Forearm wearable resistance effects on sprint kinematics and kinetics. Issue 3 (March 2019) - Macadam, Paul; Simperingham, Kim D.; Cronin, John B.
Abstract: Objectives: Arm swing is a distinctive characteristic of sprint-running with the arms working in a contralateral manner with the legs to propel the body in a horizontal direction. The purpose of this study was to determine the acute changes in kinematics and kinetics when wearable resistance (WR) of 1 kg (equivalent to ∼1% body mass) was attached to each forearm during over ground short distance (20 m) maximal sprint-running. Design: Cross-sectional study. Methods: Twenty-two male amateur rugby athletes (19.4 ± 0.5 years; 97.0 ± 4.8 kg; 180.4 ± 7.2 cm) volunteered to participate in the study. Radar and Optojump were used to examine kinematic and kinetics between WR and unloaded sprint-running conditions. Results: No significant (p < 0.05) differences were found at 2 m or 5 m between conditions, however, the WR condition resulted in a significant increase in 10 m, 20 m and 10–20 m split time (all, ∼2%, small effect size) compared to the unloaded condition. Significant decreases were also found in theoretical maximum velocity (V0 ) (−1.4%, small effect size) and relative peak horizontal power production (Pmax ) (−5.5%, small effect size). Step length (2.1%, small effect size) and contact time (6.5%, medium effect size) were significantly increased, while step frequency (−4.1%, small effect size) and flight time (−5.3%, medium effect size) were significantly decreased. Conclusions: WR forearm loading provides a movement specific overload of the arms which significantly alters step kinematics and sprint times ≥10 m.